Ballasted flotation with glass microspheres for removal of natural organic matter - Jarvis, Peter; Martin, John; Winspear, Tracey; Jefferson, Bruce (Taylor & Francis, 2013)
Low density microspheres were used to float flocs formed from the coagulation of natural organic matter (NOM) using ferric sulphate coagulant. Microspheres were visually observed to be incorporated into the floc structure during the coagulation phase. In comparison with conventional flotation with air bubbles, the residual turbidity after flotation using the microspheres was very favourable and did not impact on overall NOM removal. Spheres of the lowest density and largest particle size gave the most rapid floc clearance, but the residual turbidity after 10 minutes flotation was similar for all of the spheres investigated. The results of this work have shown that floating microspheres offer an effective, energy efficient alternative to conventional dissolved air flotation for removal of flocs containing high concentrations of NOM.